War and shadows : the haunting of Vietnam - Gustafsson, Mai Lan, 1969- (Cornell paperbacks., 2009)
The author's rich ethnographic research in Vietnam allows her to bring readers into the world of spirit possession, focusing on the source of pain, the physical and mental anguish the spirits bring, and various attempts to ameliorate their anger through ritual offering and the intervention of mediums.